CONTAMINATION OF Cd AND Pb ON MILKFISH Chanos chanos CULTURED IN SERIBU ISLANDS, JAKARTA - Etty Riani; Harry Sudrajat Johari; Muhammad Reza Cordova (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Seribu Islands located in the north of Jakarta Bay; it is potentially polluted by heavy metal such as Cd and Pb. The aims of this study is to prove contamination presumption, by analyzing and determine correlation Cd and Pb concentration in the sediment, in the water and on milkfish Chanos chanos cultured in this area. On this study, we collected water quality data (pH, temperature, dissolve oxygen and salinity) and heavy metals contamination (Cd and Pb) in the sediment, in the water and on milkfish.  We compare collected data with quality standar and correlate heavy metal concentration between in the water and in the sediment; in the water and on milkfish organ; and, in the sediment and on milkfish organ.  In general, water quality is sufficient enough to support the life of farmed milkfish. Cd and Pb contamination level in the water lied below the quality standard of Ministry of Environment decree No. 51/2004 in the last April and July. However, the contamination exceeds the standard in the last October. The contamination in sediment lied below RNO (1981), EPA (1999) and IACD/CEDA (1997). Gills, viscera and the meat of the milkfish are contaminated with Cd and Pb, yet, still lied below the quality standard of Ministry of Environment Decree No. 51/2004. The results showed that farmed milkfish in Thousand Islands are safe to eat. We also found that the correlation of Cd and Pb contamination between water and sediment is positive. The correlation of Cd is much higher than Pb. The correlation of Cd between water and viscera as well as between sediment and viscera are the most closely related than any other organ.  Keywords: contamination, Cd, farming, milkfish, Pb, Seribu Islands